LES CANCERS DIGESTIFS AU NIGER. FRÉQUENCE RELATIVE SUR UNE ETUDE RÉTROSPECTIVE DE 1992 A 2009 - Salamatou, Mamoudou G.; Hinde, Hami; Abdelmadjid, Soulaymani; Ali, Quyou; Harouna, Mahamadou Z.; Hassan, Nouhou (European Scientific Journal, ESJ, 2014)
The digestive tract cancers account for 20 % of all cancers diagnosed annually worldwide. The objective of this work is to determine the relative frequency of cancers of the digestive tract. During the study period, 594 digestive cancers were collected representing 8.44% of all cancers registered from 1992 to 2009. Sex ratio was 1.62 in favor of men. The mean age of diagnosis of cancer among the patients was 47.01 ± 15.58 years (range 1-85 years). It was clear that more than 76 % of patients came from the region of Niamey. In over 43% of cases, histological examinations have identified carcinoma after total or partial removal of tumors. In our study, the predominant tumor location was the stomach (29.29 % of cases), followed by colon (28.8%). Approximately 11.61% deaths were recorded during the study period.